Revisiting neutron scattering data from deuterated milk. (April 2021) - Smith, Gregory N.
Abstract: Deuterated milk (dried milk powder that has been dissolved in deuterated water, 2 H2 O or D2 O) is a valuable material for determining the structure of dairy products by neutron scattering. This has primarily been used in the past to study the internal structure of casein micelles, and when longer length scales have been studied, interparticle interactions have been neglected. This will impact fits to the data over all length scales, which will hamper quantitative data analysis. Previously measured large length scale neutron scattering data from the literature, both ultra-small-angle neutron scattering (USANS) and spin-echo small-angle neutron scattering (SESANS) data, have been reanalyzed and improved fits have been obtained using a recently proposed model describing casein micelles as sticky spheres, rather than as hard spheres. This shows that these interactions will also be necessary for modeling neutron scattering data on deuterated milk. Graphical abstract: Image 1 Highlights: To study interactions between casein micelles, neutron scattering techniques that probe large length scales are necessary. Fits to neutron scattering (USANS and SESANS) data are improved if casein micelles are treated as sticky spheres. This model matches the data over all length scales and provides the known amount of water within the casein micelles.